2021
DOI: 10.3389/fcvm.2021.695295
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Transcarotid Artery Revascularization With Flow Reversal System Compared to Carotid Endarterectomy: A Systematic Review and Meta-Analysis

Abstract: Background: Carotid artery stenosis has long been a critical cause of stroke and death, and it can seriously affect the life quality. Transcarotid artery revascularization (TCAR) and carotid endarterectomy (CEA) are both feasible therapies for this disease. This systematic review and meta-analysis aim to evaluate if the efficacy of the two approaches is comparable.Methods: Clinical studies up to March 2021 were searched through PubMed, Embase, and Scopus from a computer. The screening process was designed acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Moreover, they found that TCAR is associated with a lower risk of MI (P = 0.004) and CNI (P < 0.00001) than CEA. 32 Wu and associates conducted another systematic review and meta-analysis. They included 12 studies and they also find no significant difference in the risks of stroke (OR = 1.07; 95% CI, 0.83-1.37), death (OR = 1.72; 95% CI, 0.82-3.62), stroke/death (OR = 1.05; 95% CI, 0.83-1.33) and stroke/death/MI (OR = 0.95; 95% CI, 0.78-1.16) between TCAR and CEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found that TCAR is associated with a lower risk of MI (P = 0.004) and CNI (P < 0.00001) than CEA. 32 Wu and associates conducted another systematic review and meta-analysis. They included 12 studies and they also find no significant difference in the risks of stroke (OR = 1.07; 95% CI, 0.83-1.37), death (OR = 1.72; 95% CI, 0.82-3.62), stroke/death (OR = 1.05; 95% CI, 0.83-1.33) and stroke/death/MI (OR = 0.95; 95% CI, 0.78-1.16) between TCAR and CEA.…”
Section: Discussionmentioning
confidence: 99%
“…They found no statistical difference between TCAR and CEA in terms of stroke/death/MI (OR=0.85; 95% CI, 0.67–1.07), stroke (OR=1.03; 95% CI, 0.77–1.37), or death (OR=1.14; 95% CI, 0.67–1.94). Moreover, they found that TCAR is associated with a lower risk of MI ( P =0.004) and CNI ( P <0.00001) than CEA 32 . Wu and associates conducted another systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[22] TCAR has a similar prognosis to CEA and can be performed without running the risk of myocardial infarction. [29] Here, we reviewed the literature on carotid artery stenosis, CAS, CEA, TCAR, as well as emerging innovation to provide support when making clinical decisions for treatment. For lesser degrees of stenosis, CAS is often performed and CEA is only done if the need arises.…”
Section: Discussionmentioning
confidence: 99%
“…This preference is backed by its association with lower stroke and death rates and significantly fewer new lesions on diffusion-weighted magnetic resonance imaging (MRI) compared to CAS with distal protection, as demonstrated in recent studies. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…This preference is backed by its association with lower stroke and death rates and significantly fewer new lesions on diffusion-weighted magnetic resonance imaging (MRI) compared to CAS with distal protection, as demonstrated in recent studies. [6,7] Despite being an innovative and minimally invasive procedure, the cerebrovascular flow dynamics during TCAR procedures have not been thoroughly elucidated. The "flow reversal" concept is better understood by examining alterations in intracranial circulation and embolic events using transcranial Doppler (TCD).…”
mentioning
confidence: 99%